LOGO AQUA DARI PERSPEKTIF ESTETIKA DEWITT H. PARKER - Dian Sari, Nani; Magdalena Daely, Maria (CREATIVA SCIENTIA, 2025)
A visual identity can represent an entity through visual communication. Visual communication can be done in various forms, one of which is a logo. A logo becomes a visual identity that can convey the ideas, vision and mission of an entity so that it can be recognized by many people. The AQUA logo is the visual identity of AQUA mineral water that can be recognized and remembered by the wider public. An attractive identity that makes AQUA accepted in society with the right communication approach from the logo. In this research, the method used is a qualitative descriptive method. This research aims to determine the value of beauty conveyed in the AQUA logo using Parker's aesthetic perspective. Based on the research results, it can be concluded that the AQUA logo design meets DeWitt H. Parker's aesthetic principles in creating an effective and easily recognized design. From clear unity, balance, suitability of themes and appropriate levels, every element in the AQUA logo contributes to strengthening the brand message as a fresh, clean and reliable drinking water product.